2008
DOI: 10.1007/s10459-008-9122-6
|View full text |Cite
|
Sign up to set email alerts
|

Educational support group in changing caregivers’ psychological elder abuse behavior toward caring for institutionalized elders

Abstract: Institutionalized elderly who are frail and dependent are vulnerable to be abused by overwhelmed caregivers especially caregiver psychological abusive behavior is a growing but hidden problem with few evidence-based interventions. The purpose of this study was to examine the effectiveness of an educational support group in alleviating caregiver's psychological abusive behavior, reducing work stress and promoting knowledge of geriatric care-giving among a group of caregivers. A quasi-experimental design using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 22 publications
(31 reference statements)
1
43
0
3
Order By: Relevance
“…All of the studies we identified [36][37][38][39][40][41][42][43][44][45] were heterogeneous and had substantial limitations, and it is therefore difficult to recommend any of the studied interventions.…”
Section: What Evidence Supports Interventions To Combat Elder Abuse?mentioning
confidence: 99%
“…All of the studies we identified [36][37][38][39][40][41][42][43][44][45] were heterogeneous and had substantial limitations, and it is therefore difficult to recommend any of the studied interventions.…”
Section: What Evidence Supports Interventions To Combat Elder Abuse?mentioning
confidence: 99%
“…Das im Oktober 2014 in Kraft getretene Wohn-und Teilhabegesetz besagt, dass Einrichtungen der Altenpflege dazu verpflichtet sind, Maßnahmen zur Gewaltprävention durchzuführen und die Beschäftigten zur Vermeidung von Gewalt entsprechend zu schulen [25]. Eine Interventionsstudie aus Taiwan liefert Hinweise, dass Gruppenschulungsprogramme für Pflegekräfte zu einer Reduzierung psychischer Gewalt und zu einer Verbesserung in geriatrischer Pflege führen [12]. Ursachen und Risikofaktoren, die das Auftreten von Gewalt gegenüber Pflegebedürfti-gen begünstigen, sind bekannt.…”
Section: Gewaltprävention In Einrichtungen Derunclassified
“…Trotz einiger Kenntnisse zum Umgang mit gewaltbegünstigenden Faktoren beklagten die Befragten einen Mangel an Fortbildungsveranstaltungen zum Thema Gewalt, über die nur als singuläre Ereignisse berichtet wurde. Dabei gibt es wissenschaftliche Hinweise, dass Gruppenschulungsprogramme für Pflegekräfte zur Reduzierung von psychischer Gewalt und zu einer Kenntniszunahme in der geriatrischen Pflege führen können [12]. Allerdings liegen für Deutschland hierzu keine validen Daten vor; es mangelt an kontrollierten Interventionsstudien [26].…”
Section: Fortbildungenunclassified
“…Hsiu-Fang Hsieh and colleagues examined an educational support group targeting the psychological abusive behavior of staff (referred to as caregivers for this study) in institutional settings in China (Hsieh et al 2009). Using a quasi-experimental design with a case control prepost test approach, 100 participants with 50 staff caregivers in each group were assessed using the Caregiver Psychological Elder Abuse Behavior Scale (CPEAB) scale, the Work Stressors Inventory, and the Knowledge of Gerontology Nursing Scale.…”
Section: Ean Education In Institutional Settingsmentioning
confidence: 99%